Ring expansion and N,N-dimethylformamide-solvation of the cyclodimeric complex bis(3-pyridyl)dimethylsilanedicholoropalladium(II) - Kim, Cho Rong; Kang, Hyun Ji; Kim, Chi Won; Yoo, Kyung Ho; Jung, Ok-Sang (SPRINGER, 2009)
The reaction of (COD)PdCl2 (COD = 1,5-cyclooctadiene) with (3-Py)(2)SiMe2 (bis(3-pyridyl)dimethylsilane) in acetone produces single crystals consisting of cyclodimers, [PdCl2((3-Py)(2)SiMe2)](2), whereas the similar reaction in a mixture of dichloromethane and ethanol yields amorphous submicrospheres consisting of cyclotrimers, [PdCl2((3-Py)(2)SiMe2)](3). In a boiling chloroform solution, the cyclodimers are completely converted to the cyclotrimers. The structures of both cyclic species are locked at temperatures below 0 A degrees C. The cyclotrimer equilibrates to the cyclodimer, the cyclotrimer, and cyclotrimeric mono-DMF adduct, [Pd3Cl5(DMF)((3-Py)(2)SiMe2)(3)]Cl in the mole ratio of 6:1:5 in DMF solution at room temperature. The cyclodimer finally reaches the equilibrium in the same condition.
Keywords: STRUCTURAL-PROPERTIES; CYCLOTRIMER; ASSEMBLIES; CF3SO3; CARBON; METAL; PF6